Identification of chili varieties (Capsicum annum) tolerance to root cutting based on stress selection indices and morphological traits planted in lowland area - SARLIN KUSUMANINGRUM; ENDANG SULISTYANINGSIH; RUDI HARIMURTI; KUMALA DEWI (Society for Indonesian Biodiversity, 2024)
Abstract. Kusumaningrum S, Sulistyaningsih E, Harimurti R, Dewi K. 2024. Identification of chili varieties (Capsicum annum) tolerance to root cutting based on stress selection indices and morphological traits planted in lowland area. Biodiversitas 25: 2063-2073. Root cutting is a potential technique for inducing root growth to increase chili yield. A set of four lowland chili varieties were evaluated under root cutting to identify tolerant variety. Stress selection indices such as stress tolerant level (TOL), Stress Susceptible Index (SSI), Stress Tolerance Index (STI), Yield Stability Index (YSI) and morphological traits responses were employed in screening of the variety. The research was arranged in randomized complete block design factorial, where the first factor was the lowland chili varieties ('Tanjung', 'Lembang-1', 'Tanjung-2', 'Ungara'), and the second factor was period of root cutting (0, 8, and 0 + 8 weeks after transplanting and no root cutting). The results showed that 'Kencana', 'Lembang-1', 'Ungara' were identified as the tolerant group under root cutting treatment and 'Tanjung-2' was identified as the intolerant group based on chili yield and stress selection indices. The tolerant group had chili yield increment under root cutting (0, and 8 WAT), which related to high root morphological traits (root diameter, root length, root surface area, and root dry weight density). Root cutting at 8 WAT gave the highest chili yield in tolerant group. The increased root growth in the tolerant group was contributed to promote shoot morphological traits (leaf number, leaf area, and plant height). Root cutting treatment in the intolerant group caused chili yield decrement, which was related to no increment of the root and shoot morphological traits. It was concluded that root cutting treatment at 8 WAT on tolerant group ('Kencana', 'Lembang-1', 'Ungara') can be used to increase chili yield in lowland areas.